Erasing “Knowable Communities”: From Saturday Night and Sunday Morning to Brassed Off - Piskorz, Artur (Text Matters: A Journal of Literature, Theory and Culture, 2023)
The paper discusses cinematic representations of working class communities in British cinema from the pre-war documentary movement to (post-)Thatcher feature films chronicling the decline of traditional industries. A particular focus is given to contrasting Karel Reisz’s Saturday Night and Sunday Morning and Mark Herman’s Brassed Off. The former title serves as a model example of British New Wave cinema, marking the “discovery” of the working class with its “knowable communities” that revealed them to the general public. The latter film provides an apt illustration of the impact and consequences of Thatcherism on the very same communities. The paper elaborates on selected narrative and visual motifs, investigating the ways in which British filmmakers have striven to depict social changes in British society over the consecutive decades.